Monitoring South-South Cooperation (from October 2014 to April 2015) - Surasky, Javier (Revista Española de Desarrollo y Cooperación, 2023)
Current debates in international development cooperation and South-South Cooperation are spinning around two central issues: the Post 2015 Agenda and the financing for development, shifting the central debates to the themes of traditional Agenda. The 60 years since the Afro-Asian Conference in Bandung, origin of South-South Cooperation (celebrated during the period under review) remind us of the importance of coordinating positions on international processes in which the chances of success isolated are nil.